Existence of Positive Solutions for a Coupled System of (p, q)-Laplacian Fractional Higher Order Boundary Value Problems - K.R. Prasad; B.M.B. Krushna; L.T. Wesen (International Journal of Analysis and Applications, 2015)
In this paper, we establish the existence of at least three positive solutions for a system of (p,q)-Laplacian fractional order two-point boundary value problems by applying five functionals fixed point theorem under suitable conditions on a cone in a Banach space.